ATTITUDES OF STUDENTS TOWARDS THE DEAF AND HARD OF HEARING INCLUSIVE SECONDARY EDUCATION - Roy S. Daz (Proceedings of International Conference on Special Education, 2021)
The research centers on determining the attitudes of students towards the deaf and hard of hearing (DHH) inclusive secondary education. The study was conducted at La Salle Green Hills Adult Night High School in School Year 2019-2020. The researcher of the study used the purposive sampling technique in choosing its DHH respondents and convenience sampling technique in choosing its hearing students and teacher respondents. This study made use of the descriptive method of research design in the hope of seeking and describing the current status of the variables involved in the study. On the basis of the findings in this study, the researcher concludes that (a) both hearing students and DHH students have a strong positive cognitive attitude towards inclusion, (2) both hearing students and DHH students have a strong positive affective attitude towards inclusion, (3) DHH students have a positive behavioral attitude towards inclusion while hearing students have a strong positive behavioral attitude, and (d) there is no significant difference between the overall attitudes of the respondents toward DHH inclusive secondary classroom. This implies that both respondents have common cognitive, affective, and behavioral actions in an inclusive secondary education. Awareness/orientation programs, faculty development sessions, more collaborative activities between hearing and DHH learners, sign language classes, training for interpreters in the subjects they are assigned to, and involvement of parents and guardians in the program are thought to be needed by the students and teachers of the school.